Expansion of the universe and its correlation with dark energy - Tiwari, Puja; M.N Bandyopadhyay, Prof .; Chatterjee, Satakshi; S. N. Bandyopadhyay, Prof. (International Journal of Advanced Astronomy, 2020)
The Universe is expanding and science has got the relevant amount of evidence to prove that. The red shift of the distant galaxies prove that the Universe is expanding and at a good rate. The trouble is not with the expansion rather the force that is helping in this expansion. The Four Forces that is understood by physics are Gravitational Force, Electromagnetic Force, The Weak Force and The Strong Force. The four forces mentioned above unfortunately does not help in understanding the expansion of the Universe even after 13.8 billion years from the Big Bang. Initially it was thought that the Universe had an exponential expansion just after the Big Bang and this expansion will slow down before Gravity starts contracting the Universe. Well this theory got a setback after the Red Shift of the Galaxies showed that the Universe is still expanding.The expansion is happening still which means that the Gravitational Force is not being able to drift the galaxies towards one another. So what could be the unknown force that is repelling the galaxies from one another? Scientists have been working on this issue and many new concepts have been developed. Many scientists have argued that there is some force that is repelling the Universe but understanding this force has been difficult till now. Major scientists now agree that there is a force that is repelling the Universe and this force is not the four fundamental forces that are known to us. They have termed this force as the Dark Energy.What is this Dark Energy is a haunting question in todayâ€™s world. Only around 5% of the observable Universe is known till date. The rest around 95% is still a mystery to us. Of that 95% around 68% is Dark Energy. So the importance of understanding this force is the need of the hour. This force can tell a lot about the formation of the Universe from the start or it can even enlighten us if the Universe is eternal.The issue is as of now, this Dark Energy is hypothetical in nature as it has not been seen or felt by the instruments available to science today. The idea of Dark Energy goes to explain the expansion of the Universe, if Dark Energy is taken as some sort of Anti- Gravitational Force.Einsteinâ€™s theory of relativity talks of how space and time is intermingled with gravity. According to this theory space time gets modified due to the amount of matter that falls into the space. So if a planet sits on a space in the Universe it will cause a deviation in the space time field in such a way that it will accommodate the matter of the planet. So Einstein placed time as the fourth dimension and showed its importance in space. This theory stands true in majority of the cases in the Universe. The only hurdle being that inside the Black Hole this theory falters.Einstein and Schrodinger did interact with one another after he had understood that the Universe was expanding through the theory presented by Hubble. Earlier Einstein had stated that the Universe was Static. To counter the exigency that space time changes with matter he had proposed a constant by the name Cosmological Constant. Later he took the constant away stating that it was his blunder not to understand that the Universe was Expanding. Schrodinger had proposed to put the Cosmological Constant in the right side of the equation. This meant the constant may change with time and be considered more of a variable force. Though, Einstein later did not agree to the idea. Still it can be considered that both of them were talking about an extra force but could not come to any conclusion on this.Einstein in his special relativity theory had talked of conversion of energy to matter with his famous equation, E=mc^2. This meant that energy can be formed by matter and matter can be converted into energy. Though energy created from matter can be seen in Atom Bomb but matter created from energy is not seen. This paper will try to show how matter can be created from energy where Dark Energy acts as a Catalyst.This paper also tries to analyze the concept of Dark Energy as a non interacting supermassive energy (NISE). The paper will try to see the relationship between expanding Universe and Dark energy. The paper will try to develop a new spectrum that can make Dark Energy or NISE as stated in the paper visible or understandable. The paper will also like to see the relationship between Dark Energy and Photon. The paper will try to show how energy is converted from matter with the help of Dark Energy.Â